Increased severity of closed head injury or repetitive subconcussive head impacts enhances post-traumatic headache-like behaviors in a rat model. (October 2020) - Bree, Dara; Stratton, Jennifer; Levy, Dan
Introduction: Posttraumatic headache is one of the most common, debilitating, and difficult symptoms to manage after a traumatic head injury. The development of novel therapeutic approaches is nevertheless hampered by the paucity of preclinical models and poor understanding of the mechanisms underlying posttraumatic headache. To address these shortcomings, we previously characterized the development of posttraumatic headache-like pain behaviors in rats subjected to a single mild closed head injury using a 250 g weight drop. Here, we conducted a follow-up study to further extend the preclinical research toolbox for studying posttraumatic headache by exploring the development of headache-like pain behaviors in male rats subjected to a single, but more severe head trauma (450 g) as well as following repetitive, subconcussive head impacts (150 g). In addition, we tested whether these behaviors involve peripheral calcitonin gene-related peptide signaling by testing the effect of systemic treatment with an anti-calcitonin gene-related peptide monoclonal antibody (anti-calcitonin gene-related peptide mAb). Methods: Adult male Sprague Dawley rats (total n = 138) were subjected to diffuse closed head injury using a weight-drop device, or a sham procedure. Three injury paradigms were employed: A single hit, using 450 g or 150 g weight drop, and three successive 150 g weight drop events conducted 72 hours apart. Changes in open field activity and development of cephalic and extracephalic tactile pain hypersensitivity were assessed up to 42 days post head trauma. Systemic administration of the anti-calcitonin gene-related peptide mAb or its control IgG (30 mg/kg) began immediately after the 450 g injury or the third 150 g weight drop with additional doses given every 6 days subsequently. Results: Rats subjected to 450 g closed head injury displayed an acute decrease in rearing and increased thigmotaxis, together with cephalic tactile pain hypersensitivity that resolved by 6 weeks post-injury. Injured animals also displayed delayed and prolonged extracephalic tactile pain hypersensitivity that remained present at 6 weeks post-injury. Repetitive subconcussive head impacts using the 150 g weight drop, but not a single event, led to decreased vertical rearing as well as cephalic and extracephalic tactile pain hypersensitivity that resolved by 6 weeks post-injury. Early and prolonged anti-calcitonin gene-related peptide mAb treatment inhibited the development of the cephalic tactile pain hypersensitivity in both the severe and repetitive subconcussive head impact models. Conclusions: Severe head injury gives rise to a prolonged state of cephalic and extracephalic tactile pain hypersensitivity. These pain behaviors also develop following repetitive, subconcussive head impacts. Extended cephalic tactile pain hypersensitivity following severe and repetitive mild closed head injury are ameliorated by early and prolonged anti-calcitonin gene-related peptide mAb treatment, suggesting a mechanism linked to calcitonin gene-related peptide signaling, potentially of trigeminal origin.